Rank and Two Aspects of Dress in Elizabethan England - McCracken, Grant (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1982)
As a contribution to the nascent field of historical anthropology, this paper considers the relation between two aspects of Elizabethan dress and the social order of early modern England. Both the sumptuary legislation which governed dress, and the ornamentation which adorned it are seen to articulate and reconcile the conflicting principles out of which the Elizabethan hierarchy was created. In conclusion, it is suggested that dress and other material aspects of culture assume a special significance for the historical anthropologist. Deprived of verbal testimony, the historical anthropologist must attach new importance to the extant objects in which the ideas, preoccupations and contradictions of culture still adhere.